Vulvar swelling as the first presentation of Crohn's disease in children—A report of three cases. Issue 1 (21st November 2017) - Ahad, Tashmeeta; Riley, Anna; Martindale, Elizabeth; von Bremen, Beate; Owen, Caroline
Abstract: Vulvar swelling is a rare manifestation of metastatic Crohn's disease in children. It often predates gastrointestinal symptoms and can be the first presentation of pediatric Crohn's disease. We report three cases of pediatric Crohn's disease presenting with vulvar swelling. We discuss this rare presentation and its treatment and highlight the importance of recognizing it so that prompt investigation and appropriate management can be initiated.